Real Convergence, Capital Flows, and Competitiveness in Central and Eastern Europe - Ansgar Belke; Gunther Schnabl; Holger Zemanek (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
The paper scrutinizes the role of wages and capital flows for competitiveness in the new EU member states in the context of real convergence. For this purpose it extends the seminal Balassa-Samuelson model by international capital markets. The augmented Balassa-Samuelson model is linked to the monetary overinvestment theories of Wicksell and Hayek in order to trace cyclical deviations of real exchange rates from the productivity-driven equilibrium path. Panel estimations for the period from 1993 to 2008 reveal mixed evidence for the role of capital markets for both the economic catch-up process and international competitiveness of the Central and Eastern European countries.
Keywords: E24; F16; F32; 330; Exchange rate regime; wages; Central and Eastern Europe; EMU accession; panel model; Entwicklungskonvergenz; Internationaler Wettbewerb; Wechselkurssystem; Lohnniveau; Internationale Kapitalmobilität; Kaufkraftparität; Balassa-Samuelson Effekt; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Schätzung; EU-Staaten (Osteuropa)